B7x/B7-H4 modulates the adaptive immune response and ameliorates renal injury in antibody-mediated nephritis. (2nd January 2015) - Pawar, R D; Goilav, B; Xia, Y; Herlitz, L; Doerner, J; Chalmers, S; Ghosh, K; Zang, X; Putterman, C
Summary: Kidney disease is one of the leading causes of death in patients with lupus and other autoimmune diseases affecting the kidney, and is associated with deposition of antibodies as well as infiltration of T lymphocytes and macrophages, which are responsible for initiation and/or exacerbation of inflammation and tissue injury. Current treatment options have relatively limited efficacy; therefore, novel targets need to be explored. The co-inhibitory molecule, B7x, a new member of the B7 family expressed predominantly by non-lymphoid tissues, has been shown to inhibit the proliferation, activation and functional responses of CD4 and CD8 T cells. In this study, we found that B7x was expressed by intrinsic renal cells, and was up-regulated upon stimulation with inflammatory triggers. After passive administration of antibodies against glomerular antigens, B7x −/− mice developed severe renal injury accompanied by a robust adaptive immune response and kidney up-regulation of inflammatory mediators, as well as local infiltration of T cells and macrophages. Furthermore, macrophages in the spleen of B7x −/− mice were polarized to an inflammatory phenotype. Finally, treatment with B7x-immunoglobulin (Ig) in this nephritis model decreased kidney damage and reduced local inflammation. We propose that B7x can modulate kidney damage in autoimmune diseases including lupus nephritis and anti-glomerular basement membrane disease. Thus, B7x mimetics may be a novel therapeutic option for treatment of immune-mediated kidney disease.